2000
DOI: 10.1152/jn.2000.83.4.1840
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses to Overlapping FM Sounds in the Inferior Colliculus of Echolocating Bats

Abstract: The big brown bat, Eptesicus fuscus, navigates and hunts prey with echolocation, a modality that uses the temporal and spectral differences between vocalizations and echoes from objects to build spatial images. Closely spaced surfaces ("glints") return overlapping echoes if two echoes return within the integration time of the cochlea ( approximately 300-400 micros). The overlap results in spectral interference that provides information about target structure or texture. Previous studies have shown that two aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 50 publications
2
40
1
Order By: Relevance
“…Multiple studies have shown that various sites in the auditory pathway (e.g., inferior colliculus, auditory cortex) of frequencymodulating bats (28)(29)(30)(31), including big brown bats (32)(33)(34)(35)(36), register the brief FM sweeps in biosonar broadcasts and echoes on a frequency-by-frequency basis using responses of neurons tuned to individual frequencies distributed across the 15-100 kHz band. When big brown bats are stimulated by multiple-harmonic FM sounds of 1-to 3-ms duration, comparable to those emitted and received during flights through the chains, each neuron produces approximately one spike that marks the time-of-occurrence of that cell's best excitatory frequency along the sweep (28-36).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that various sites in the auditory pathway (e.g., inferior colliculus, auditory cortex) of frequencymodulating bats (28)(29)(30)(31), including big brown bats (32)(33)(34)(35)(36), register the brief FM sweeps in biosonar broadcasts and echoes on a frequency-by-frequency basis using responses of neurons tuned to individual frequencies distributed across the 15-100 kHz band. When big brown bats are stimulated by multiple-harmonic FM sounds of 1-to 3-ms duration, comparable to those emitted and received during flights through the chains, each neuron produces approximately one spike that marks the time-of-occurrence of that cell's best excitatory frequency along the sweep (28-36).…”
Section: Discussionmentioning
confidence: 99%
“…2.6s) following the nominal position of FM2 and extends to at least 300s later without serious deterioration of the defocusing effect. This pattern of results suggests that, when responses to FM2 are allowed to shift to a later time than normal, they activate neuronal inhibition that initiates a cascade of responses designed to register the shape of targets from echo interference spectra (see Sanderson and Simmons, 2000;Sanderson and Simmons, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The target's contribution instead consists of local notches in the spectrum due to reinforcement and cancellation caused by interference between overlapping reflections from multiple parts of the target, or glints (the target's acoustic 'shape') (Kober and Schnitzler, 1990;Moss and Zagaeski, 1994;Simmons and Chen, 1989). Behavioral, neurophysiological and computational studies have identified a process, called spectrogram correlation and transformation (SCAT), that has been hypothesized to explain how big brown bats locate the frequencies of these interference notches and reconstruct the corresponding delay differences between different parts of the target (Matsuo et al, 2004;Neretti et al, 2003;Peremans and Hallam, 1998;Saillant et al, 1993;Sanderson and Simmons 2000;Sanderson and Simmons, 2002;Sanderson and Simmons, 2005;Simmons et al, 1995;Simmons et al, 1998). Using a combination of overall echo delay and the echo interference spectrum as cues, these bats recreate for each echo an image depicting the object as a small number of glints on a perceptual axis of distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical action of the bat's cochlea disperses ultrasonic frequencies to sequential locations along the organ of Corti, creating many parallel frequency-tuned channels which segment the wideband FM sweeps of echoes into numerous overlapping time͞frequency ''slices'' (24). Within these channels, neural transduction generates single spikes that register the times-of-occurrence of different frequencies in the sweeps (25)(26)(27). At higher levels of the auditory pathway, it is likely that volleys of spikes with different latencies representing the same time͞frequency slices are used to make multiple estimates of echo delay (28).…”
Section: Methodsmentioning
confidence: 99%